Short Communication: Correlation and regression among rice panicle branches traits - TRI HASTINI; WILLY BAYUARDI SUWARNO; MUNIF GHULAMAHDI; HAJRIAL ASWIDINNOOR (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Hastini T, Suwarno WB, Ghulamahdi M, Aswidinnoor H. 2019. Short Communication: Correlation and regression among rice panicle branches traits. Biodiversitas 20: 1140-1146. Panicle was a very important organ in rice since the grains are developed from the panicle branches. This study aimed to find out the information about the relationship among rice panicle branching traits using correlation and regression analysis. The trial was conducted at the IPB Research Station, Babakan, Bogor, Indonesia from December 2015 until April 2016. Twenty genotypes of lowland rice were used as treatments with three replications and arranged in a completely randomized design. The panicle branches traits were observed. The result showed that there was positively and a highly significant relationship among the panicle branches traits in general. Analysis using linear regression revealed that, in general, the total grains number per panicle showed the linear relationships with other traits, and only total grains number per panicle vs tertiary branches number, total grains number per panicle vs grains number of tertiary panicle branch, and total grains number per panicle vs the number of secondary branches per panicle branch showed the quadratic relationship. Among all rice panicle branching traits, the secondary panicle branches number had the highest contribution to the total grains number per panicle.